CNOT7 depletion reverses natural killer cell resistance by modulating the tumor immune microenvironment of hepatocellular carcinoma. Issue 5 (2nd April 2020) - Ren, Chongren; Ren, Xiaojing; Cao, Dujuan; Zhao, Haichao; Zhai, Zhensheng; Li, Huiyu; Li, Yanjun; Fu, Xifeng; He, Jiefeng; Zhao, Haoliang
Abstract : A major obstacle to effective cancer immunotherapy is the tumor immune microenvironment. Natural killer (NK) cell resistance has been suggested as a primary cause of poor prognosis in hepatocellular carcinoma (HCC), which seemingly correlates with CNOT7 overexpression. CNOT7, a cytoplasmic mRNA deadenylase that is highly expressed in HCC, may regulate cytokine transforming growth factor‐β1 (TGF‐β1) secretion by controlling nuclear factor‐κB subunit p65 trafficking. CNOT7 depletion suppresses TGF‐β1 secretion in HCC and promotes interferon‐γ (IFN‐γ) secretion by NK cells, and we previously demonstrated that CNOT7 depletion reversed IFN‐γ resistance in HCC cells. Therefore, we hypothesized that CNOT7 depletion might reverse NK cell resistance by influencing the tumor immune microenvironment of HCC. To test this hypothesis, we examined the correlation between CNOT7, STAT1, TGF‐β1 and IFN‐γ expression with hepatitis B virus‐related cirrhosis and HCC with hepatitis B virus‐related cirrhosis. We found that modulation of CNOT7 expression alters TGF‐β1 secretion in HCC and IFN‐γ secretion in NK cells. We also examined the effects of NK cells in HepG2 cells with CNOT7 knockdown, which showed that NK cell surface CD107a expression is up‐regulated and caspase‐3 expression is significantly enhanced in CNOT7‐deficient HepG2 cells. Overall, our results show that knockdown of CNOT7 expression reverses NK cell resistance in HCC cells. Therefore, CNOT7 depletion has potential as a new adjuvant therapy in immunotherapy for HCC. Abstract : Natural killer (NK) cell resistance is a primary cause of poor prognosis in hepatocellular carcinoma (HCC), which correlates with CNOT7 overexpression. Tumor‐derived transforming growth factor‐β1 created a strong inhibitory network and impaired NK cells. CNOT7 depletion could suppress transforming growth factor‐β1 secretion by controlling nuclear factor‐κB subunit p65 trafficking in HCC. We found that CNOT7 depletion may reverse NK cell resistance in HCC cells.